Evaluation of different calibration strategies for large scale continuous hydrological modelling - M. Wallner; U. Haberlandt; J. Dietrich (Advances in Geosciences, 2012)
For the analysis of climate impact on flood flows and flood frequency in macroscale river basins, hydrological models can be forced by several sets of hourly long-term climate time series. Considering the large number of model units, the small time step and the required recalibrations for different model forcing an efficient calibration strategy and optimisation algorithm are essential.